Developing a computerized health record in a protective services system. - Smart, Jeanne; Russell, Joi; Custodio, Cecilia (Child Welfare)
A computerized health record application was incorporated into the Los Angeles County Department of Children and Family Services Child Information System (CIS) to capture information on the health status and medical needs of over 60,000 children under the department's care and supervision. The Child Health System (CHS) was designed to store health information needed by social workers to provide comprehensive services to children and their families. The CHS stored Information concerning the child's current and past health problems, allergies, health examinations, and immunizations. in addition, the CHS also maintained information on the child's educational, psychological, and developmental status, and the child's family health history. A description of the CHS's development and features, along with a brief overview of the 2,688 cases entered into the system during the first seven months of its application, are presented. Although California has recently moved to a statewide system, other jurisdictions currently computerizing their systems may learn valuable lessons from the Los Angeles County experience. Reprinted by permission of the publisher.